An Analysis of the Guidance of Futsal Extracurricular Achievements at the Bengkulu City State High School Level - Pangestu, Bima Bagus; Yarmani, Yarmani; Ilahi, Bogy Restu; Defliyanto, Defliyanto (Athena: Physical Education and Sports Journal, 2023)
This study aims to determine the guidance of futsal extracurricular achievements in Bengkulu City State Senior High Schools. This study used qualitative descriptive method to adjust the opinions between researchers and informants. The subject of this research are 11 State Senior High Schools in Bengkulu City. The instruments used are observation, questionnaires, and documentation. Based on the results pf the data obtained, the development of futsal extracurriculer achievement at the Bengkulu City hight school level is categorized as still not good with a percentage of 54,54%, from 11 schools there are 5 schools that can be stated to meet the standards of futsal extracurricular achievement guidance while 6 schools did not meet the futsal extracurricular achievement standards namely SMA Negeri 1 Bengkulu City, SMA Negeri 2 Bengkulu City. SMA Negeri 3 Bengkulu City, SMA Negeri 6 Bengkulu City, and SMA Negeri 7 City. Based on the results of this study, it can be concluded that the extracurricular achievement guidance of these 5 schools meets the standards of achievement guidance due to many factors, that is good coaching supported by a good training program, support from the school, having competent trainers, having adequate equipment facilities and having clear targets, while 6 schools have not met the standards of achievement guidance because these factors have not been fulfilled.